2004
DOI: 10.1124/jpet.103.058388
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of Organic Cation Transporters rOCT1 and rOCT2 in Experimental Diabetes

Abstract: Recent reports have documented a functional deficit of organic cation transport in diabetic rats by an unknown mechanism. This study was designed to test the hypothesis that experimental diabetes decreases expression of organic cation transporters at the basolateral membrane. Streptozotocin-induced diabetic rats were maintained for varying durations after induction of diabetes. A second group of agematched control rats was maintained in a parallel manner. Kinetic analysis of tetraethylammonium accumulation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 41 publications
2
58
0
2
Order By: Relevance
“…A decreased level of renal Oat3, but not Oat1, was observed after four weeks of diabetic condition, in agreement with earlier observations of a significant reduction in Oct expression after 4 weeks of diabetes in rats 16 . Several pathways are thought to be involved in the pathogenesis of hyperglycaemia-induced complications in diabetes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…A decreased level of renal Oat3, but not Oat1, was observed after four weeks of diabetic condition, in agreement with earlier observations of a significant reduction in Oct expression after 4 weeks of diabetes in rats 16 . Several pathways are thought to be involved in the pathogenesis of hyperglycaemia-induced complications in diabetes.…”
Section: Discussionsupporting
confidence: 80%
“…There is a significant reduction in tubular cation clearance associated with a down-regulation of the expression of tubular OCTs on the basolateral surface of the proximal tubule 15,16 . Although a reduction of the renal clearance of hippurate in diabetic patients has www.scienceasia.org been reported 17 , there is no report to date concerning the impact of the duration of hyperglycaemia on the function and expression of renal OATs.…”
Section: Introductionmentioning
confidence: 99%
“…Although species differences may explain these conflicting results, renal OCT1 protein levels were not examined in the aforementioned study (because 17␤-E 2 failed to change renal OCT1 mRNA expression in rats; Urakami et al, 2000). In diabetic rats, OCT1 protein expression is reduced without a substantial change in mRNA levels (Grover et al, 2004). In rabbits, renal expression of OCT2 mRNA is much higher in male than female rabbits; yet, there are no gender differences in OCT2 protein expression or basolateral TEA transport (Groves et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglyemia itself directly reduced the activity of Mdr1 suggesting a clear association between pre-T1D hyperglycemia and disturbances in protein transporters [66]. In another recent study, the effect of STZ on cation protein transporters was reported, interestingly, at different levels of protein synthesis; transcriptional and posttranscriptional depending on the type of the transporters affected [67]. However, some studies suggest a diabetic influence is stronger on enzymatic activities than on protein transporters with the enzymatic influence being the cause of exacerbation of inflammation and development of the disease [68].…”
Section: The Influence Of Gut Microflora On the Development Of Autoimmentioning
confidence: 98%